Intravenous immunoglobulins in children with new onset dilated cardiomyopathy. (11th August 2017) - Heidendael, Josephine F.; Den Boer, Suzanne L.; Wildenbeest, Joanne G.; Dalinghaus, Michiel; Straver, Bart; Pajkrt, Dasja
Abstract: Background: Dilated cardiomyopathy is a rare but serious disorder in children. No effective diagnostic or treatment tools are readily available. This study aimed to evaluate the efficacy of intravenous immunoglobulins in children with new onset dilated cardiomyopathy. Methods and results: In this retrospective cohort study, 94 children with new onset dilated cardiomyopathy were followed during a median period of 33 months. All patients with secondary dilated cardiomyopathy – for example, genetic, auto-immune or structural defects – had been excluded. Viral tests were performed in all patients and 18 (19%) children met the criteria for the diagnosis "probable or definite viral myocarditis". Intravenous immunoglobulins were administered to 21 (22%) patients. Overall transplant-free survival was 75% in 5 years and did not differ between treatment groups. The treatment was associated with a higher recovery rate within 5 years, compared with non-treated children (70 versus 43%, log rank=0.045). After correction for possible confounders the hazard ratio for recovery with intravenous immunoglobulins was not significant (hazard ratio: 2.1; 95% CI: 1.0–4.6; p=0.056). Administration of intravenous immunoglobulins resulted in a greater improvement in the shortening fraction of the left ventricle. Conclusion: In our population of children with new onset dilated cardiomyopathy, of either viral or idiopathic origin, intravenous immunoglobulins were administered to a minority of the patients and did not influence transplant-free survival, but were associated with better improvement of systolic left ventricular function and with better recovery. Our results support the concept that children with new onset dilated cardiomyopathy might benefit from intravenous immunoglobulins.